13+3=-4(8x-4)

Simple and best practice solution for 13+3=-4(8x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+3=-4(8x-4) equation:



13+3=-4(8x-4)
We move all terms to the left:
13+3-(-4(8x-4))=0
We add all the numbers together, and all the variables
-(-4(8x-4))+16=0
We calculate terms in parentheses: -(-4(8x-4)), so:
-4(8x-4)
We multiply parentheses
-32x+16
Back to the equation:
-(-32x+16)
We get rid of parentheses
32x-16+16=0
We add all the numbers together, and all the variables
32x=0
x=0/32
x=0

See similar equations:

| 23-(n-13)=6(n+5) | | -5x+x/22=-1 | | 9a-2=8a+2 | | m-9.3=13.6 | | –7r=–7−6r | | q5–-19=22 | | 16-5x=5(3x+7)+1 | | 8+2(x+2)=x+14 | | 9x-6x+10=40+x+12 | | 18=-6d-6d-6 | | q5− –19=22 | | m=-9-2m | | m=306 | | 4(n+6)=2(3-7n) | | -2c-5(c-6)=-47 | | 2(4x+8)=-41+9 | | -c+10=-10+4c-10 | | √u-5=6 | | 5x+3-(x+51)=180 | | z/9+3=-69 | | 3(r+1)-5=-3+2r | | 1+7w=-5+3w+2 | | 8=6q-8q | | 4(5x+8)=-34+26 | | z+1=-7+9z | | -2y-3=-45 | | 3c-12=6 | | z/9+3=-25 | | 56=16-10(8+b) | | 185-y=282 | | -4+8b=4b | | (2g-2)4g-9=133 |

Equations solver categories